Determining the effectiveness of prophylactic topical silver dressings in the treatment of sacrococcygeal pilonidal sinus wounds healing by secondary intention - Edmondson, Margaret (Curtin University, 2013)
A randomised controlled trial was conducted to determine if the prophylactic use of nanocrystalline silver alginate (SA) dressings could reduce the healing time for sacrococcygeal pilonidal sinus wounds healing by secondary intention.The SA dressing group had a mean time to wound healing of 46 days as compared to 66 days for the calcium alginate dressing group. On average, a 20% greater reduction in wound size was achieved with the SA dressing group.